Borgesian Libraries and Librarians in Television Popular Culture - Iana Konstantinova (Studies in 20th & 21st Century Literature, 2013)
In the works of Jorge Luis Borges, the library appears frequently as a metaphor representative of life and its secrets. It becomes a metaphysical location, posing questions about the nature of time, life, and the universe itself. The librarian becomes a metaphysical figure, leading the search for answers to life’s questions. This article examines the way in which the Borgesian library metaphor has crossed over from the realm of literature into the realm of popular television. By examining two episodes of the BBC series Doctor Who, the TNT franchise The Librarian, and several episodes of Joss Whedon’s cult television series Buffy the Vampire Slayer, it demonstrates that the metaphysical questions posed by the library and its librarian in Borges’s short stories are quite similar to the metaphysical questions posed by the library and its librarians in popular television, demonstrating that the Borgesian library has crossed over into the realms of popular culture.
Keywords: Jorge Luis Borges; library; Buffy the Vampire Slayer; The Librarian; Doctor Who